Meningkatkan Pengetahuan Masyarakat Mengenai Hipertensi Dengan Metode Penyuluhan Menggunakan Media Audio Visual - Nurhidayat, M. Arif (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Hypertension is a chronic disease that is often found in all levels of society with the main factor being cardiovascular disease. The main causes of this disease are genetics, lifestyle changes and stress. If hypertension is not treated immediately, it will certainly cause complications such as kidney problems, stroke and increase the risk of cardiovascular disease. Classification of hypertension according to WHO: normal blood pressure: 90-120 mmHg, pre-hypertension: 120-139 mmHg, grade 1 hypertension: 140-159 mmHg and grade 2 hypertension: more than 160 mmHg. The phenomenon that is often encountered is the level of knowledge about hypertension. Many people still do not know about the causes, signs and symptoms or how to treat hypertension. Hypertension cases are increasing every year, so there is a need for health efforts as a preventive measure. This community service was carried out in Tunjungnjagir Village, which is one of the villages located in Mantup District, Lamongan Regency. The aim of this community service in the form of socialization is to increase public knowledge about hypertension. The method used is a lecture method followed by a question and answer session using audiovisual media and leaflets. The results of this community service show an increase in the average value of hypertension knowledge from 79.6 to 86.9 after being given health education. Service activities in the form of health education can improve the quality of life by introducing the principles of prevention and are expected to reduce the prevalence of the disease itself.